Eco-Enzyme Bar Soap Making Training as an Effort to Increase Creativity: Pelatihan Pembuatan Sabun Batang Eco-Enzyme Sebagai Upaya Meningkatkan Kreativitas - Elma Suryani; Elsa Vera Nanda; Edith Allanas (Universitas Lancang Kuning, 2025)
This activity aims to improve the creativity of chemistry teachers through eco-enzyme soap making training. The method used includes three stages, namely the preparation stage, the implementation stage and the evaluation stage. The results of the post-training evaluation showed that 89% felt they had gained new insights and knowledge and 91% stated that the material presented was relevant and in accordance with expectations, while creativity was measured by an instrument using 4 indicators, namely 75% stated that they were able to produce ideas, 83% stated that they were able to explore ideas deeper, 80% stated that they were able to explore the ideas produced, and 76% stated that they listened to their inner voice when producing creative ideas. This activity has a positive impact because it can increase the insight and creativity of chemistry teachers in project-based learning.